Association of Atrial Fibrillation with White Matter Disease: The Atherosclerosis Risk in Communities (ARIC) Study - Shao, Iris Yuefan (Stroke, 2019)
BACKGROUND AND PURPOSE: Evidence suggests that atrial fibrillation (AF) is associated with increased risk of cognitive decline and dementia, even in the absence of stroke. White matter disease (WMD) is a potential mechanism linking AF to cognitive impairment. In this study, we explored the association between prevalent AF and WMD. METHODS: We performed a cross-sectional analysis of participants attending the ARIC-Neurocognitive Study in 2011–2013 who underwent brain magnetic resonance imaging. AF was ascertained from study visit electrocardiograms or prior hospitalization codes. Extent of WMD was defined by measures of white matter microstructural integrity and white matter hyperintensity (WMH) volume. Multivariable linear regression models were used to assess the association between AF and WMD. RESULTS: Among 1899 participants (mean age 76 years, 28% black, 60% female), 133 (7%) had prevalent AF. After multivariable adjustment, differences between participants with and without AF were −0.001 (95% confidence interval (CI) −0.006, 0.004) for global white matter fractional anisotropy, 0.031*10(−4) mm(2)/s (95%CI −0.075, 0.137) for global white matter mean diffusivity, and 0.08 mm(3) (95%CI −0.14, 0.30) for WMH volume. CONCLUSIONS: The results suggest that there is no association between prevalent AF and WMD.